(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Acute kidney injury (AKI) is a common complication of coronary artery bypass graft with several serious complications. This study aimed to find the incidence of AKI after coronary artery bypass graft and its complications based on the Acute Kidney Injury Network (AKIN) criteria. Materials and Methods. This study was done on 3470 patients who had undergone isolated coronary artery bypass graft. Acute kidney injury’s incidence was based on the AKIN criteria (only based on serum creatinine irrespective of urine output). Patients’ demographic data, in-hospital complications, and out-hospital mortality were collected from hospital databases and compared between the patients with and without AKI. Results. Based on serum creatinine, the incidence of AKI was 27.7% (958 patients) on the 1st postoperative day. Nine patients (0.3%) needed hemodialysis during their hospital stay, and 31 patients (0.7%) developed persistent kidney failure until the discharge day. The number of patients undergoing hemodialysis was not significantly difference but persistent kidney failure was significantly more frequent in patients with AKI (P < .001). Those with AKI also experienced longer length of stay (P = .04) and longer length of stay in intensive care unit (P < .001), and their mortality rate was higher in hospital (P < .001) and during the 3-year follow-up period (P < .001). Conclusions. Although AKI is associated with great patients’ morbidity and in-hospital and long-term mortality, most of AKI episodes after coronary artery bypass graft are mild with no need for hemodialysis, and they mostly improve spontaneously.